An examination of non-linear and passive technology transfer in the space sector: Consideration of the Contingent Effectiveness Model as a basis for formal modeling. (November 2016) - Smart, Jordan; Benaroya, Haym
Abstract: Technology transfer has been a cornerstone of the justification for public expenditure of space technology development programs since at least the creation of NASA out of its predecessor agencies. Research into its mechanisms has, however, been largely qualitative and focused on actively managed, one-way transfer of technology from agencies to industry. In this paper we consider the effects of a wider range of mechanisms by which space agencies affect the technical knowledgebase, and examine the Contingent Effectiveness Model as a useful framework for formalizing comparative analysis of transfers.